Impact of inclusion into and exclusion from the Shariah index on a stock price and Trading Volume: Event study approach - Kassim, Nawal Seif; Ramlee, Roslily; Kassim, Salina (Econjournals, 2017)
Does the inclusion or exclusion from the Shariah index have any effect on the performance of a stock? This study aims to examine the impact of stock inclusion (or exclusion) on the stock prices and trading volume of the firms. Based on the case of selected stocks in Bursa Malaysia, our sample consists of 107 additions and 95 deletions from the FTSE Bursa Malaysia Emas Shariah Index (FBMESI) in the period June 2007-June 2014. Event study methodology is used to estimate the abnormal returns and abnormal volumes in the days surrounding the announcement and change dates. The study finds the included stock shows significant and permanent excess returns and abnormal volumes. On the other hand, deleted stocks earn temporary significant negative returns and below normal volumes after the announcement and change dates.